"Let the Red Terror Intensify": Political Violence, Governance and Society in Urban Ethiopia, 1976-78 - Wiebel, Jacob (The International journal of African historical studies, 2015)
The Ethiopian Terror years have been written about and memorialized as a period of sustained state terror.1 The EPRDF's "Red Terror trials," which ran for the better part of two decades following the overthrow of the Derg 2 limited themselves to the prosecution of violence carried out in the name of the state and assumed considerable centralized control in their verdicts on senior government figures.3 Similarly, the "Ethiopian Red Terror Martyrs' Memorial Museum," which opened in Addis Ababa's Meskel Square in 2010, conveys a simple narrative of state perpetrators and civilian victims, with no regard to shifts in agency and mode of violence. [...]of this process, the Ethiopian Terror was never merely a conflict between competing political groups.